IMPLEMENTASI KEBIJAKAN BEA MASUK ANTI DUMPING INDONESIA TERHADAP IMPOR PRODUK TEKSTIL SPIN DRAWN YARN (SDY) DARI CHINA TAHUN 2019 - Sari Indah Pratama; Umi O. Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Dumping is one of the issues in international trade. The problem of dumping can cause injury even shut down the domestic industry, this injury certainly has a big impact to the country. This thing happened in Indonesia in the case of dumping imported textile product, namely Spin Drawn Yarn (SDY) from China. The complaints of the domestic industry and Indonesia Fiber and Filament Yarn Producer Association (APSyFI) became the basis for an investigation conducted by Indonesian Anti-Dumping Commission (KADI). In this research, author will describe KADI’s investigation to the effectiveness of the implementation of BMAD. This study uses a mercantilism approach with protectionism theory, where the state protects the domestic industry through policies issued in accordance with the imposition of BMAD on imports of SDY products from China. The method used in this study is a qualitative method with data collection techniques in the form of primary data by interviewing the Sub-Committee on Investigation of the Evidence of Dumping and Subsidy of the Indonesian Anti Dumping Committee and APSyFI Industry and Trade Analyst, and using secondary data from books, journals, government regulations, reports, news and websites. The results of this study indicate that the imposition of Anti-Dumping Duties on imported SDY products from China has succeeded in reducing the volume imports, so the local producers as domestic industry can compete with similar imported products. These protective measures are effective in protecting local industries from dumping practices, which can be seen from the reduction in the volume of SDY imports from China and the recovery of domestic industry. Keywords : BMAD, Policy, Protection, SDY, Imports.